TAFRO syndrome associated with C3 nephropathy (an analysis of clinical experience) - I. V. Pozharov; A. O. Grigorevskaya; G. R. Setdikova; E. S. Stolyarevich (Klinicist)
Aim. To present a clinical case of TAFRO syndrome – a recently described subtype of idiopathic multicentric Castleman disease of unknown etiology, characterized by thrombocytopenia, anasarca, fever, reticulin fibrosis of the bone marrow and / or renal dysfunction, organomegaly associated with an increase in serum IL-6 secretion.Materials and methods. Herein, we report a young patient diagnosed with TAFRO combined with C3 nephropathy. The patient was treated with glucocorticoids (methylprednisolone), colchicine, sarilumab, rivaroxaban, and symptomatic treatment.Results. Key aspects of diagnosis, treatment and course of the syndrome were discussed. The possibility of the combined course of two rare pathologies – a subtype of idiopathic multicentric Castleman disease and C3 nephropathy is still unclear.Conclusion. The diagnosis of TAFRO syndrome can be considered after the exclusion of a number of infectious, paraneoplastic, systemic connective tissue diseases, POEMS syndrome, liver cirrhosis against the background of autoimmune hepatitis, autoimmune thrombocytopenic purpura, as well as hemolytic-uremic syndrome. Kidney damage in this category of patients, in most of the described clinical cases, is morphologically represented by thrombotic microangiopathy or mesangioproliferative glomerulonephritis. C3 nephropathy in that clinical case seems to be concomitant. Glucocorticoids in high and ultrahigh doses, cyclosporine, IL-6 type inhibitors, as well as anti-CD20 antibodies are used as therapy.